FARMA: uma ferramenta de autoria para objetos de aprendizagem de conceitos matemáticos - Marczal, Diego (2014)
Nowadays the technology is essencial to the process of teaching and learning and one of the prominent approaches is the use of Learning Objects. Seeing that, the research developed a web authoring tool to Learning Objects, which allows the manipulation of the error records in the teaching practice through retroaction mechanism that allows going back to the context of correct and wrongs interactions of apprentices. Thus, it is argued that the storage, visualization, manipulation, and retrieval of errors records and also correct interaction of the learners can bring benefits for teaching and learning. In this thesis, the problem of building learning objects with authoring tools is exposed in a critical way. The main limitations of current approaches to mathematics teaching with learning objects are pointed out in the literature review. A web authoring tool, called FARMA, focusing on the concept of techno-educational mobility, is presented as an alternative to existing pedagogic approaches that rely on technological devices, the theory Adaptive Control of Thought guided the fellowship model creation and presentation of the proposed framework exercises. The mistakes of the learner are highlighted as a central cognitive approach of learning in the current version of FARMA. The evaluation of the authoring tool was done as an empirical study focused on simplicity to create mathematical Learning Objects. The experiment conducted to evaluate a new approach of working with errors in Learning Objects focused in the use by teachers and learners and their potential benefits for teaching and learning. The results show that the framework developed with the proposed use of errors in the acquisition of knowledge, fundamentally di!erent from those found in environments educacionas process, has great potential for teaching and learning.